Unbearable weight: Feminism, western culture, and the body - Bordo, Susan (University of California Press, 2003)
Susan Bordo untangles the myths, ideologies, and pathologies of the modern female body. Bordo explores our tortured fascination with food, hunger, desire, and control, and its effects on women's lives
Keywords: 2000-2009; 2000-2029; corps; discipline; fem1000; image corporelle; occident; philosophie; premier cycle; périodes historiques; sciences humaines; thématiques; études culturelles

Le contrôle de notre corps est politique - Coordination nationale pour l'avortement libre et gratuit; Gaucher, Dominique (La pensée féministe au Québec: Anthologie 1900-1985, 2003)
Keywords: 1900-1999; amériques; avortement; corps; droits des femmes*; fem1000; justice reproductive; militance; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; santé reproductive; thématiques; violences

D'Eros, des poissons et des femme - Pelletier, Francine (La pensée féministe au Québec. Anthologie (1900-1985), 2003)
Keywords: 1900-1999; amériques; corps; fem1000; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; sexualité; thématiques